Stand structure, diversity, and carbon stock assessment of Lake Duluti Forest Reserve in Tanzania - UPENDO SHWAIBU MFINANGA; EZEKIEL EDWARD MWAKALUKWA (Nusantara Bioscience, 2025)
Abstract. Mfinanga US, Mwakalukwa EE. 2025. Stand structure, diversity, and carbon stock assessment of Lake Duluti Forest Reserve in Tanzania. Nusantara Bioscience 17: 185-193. For a successful conservation of biodiversity in a particular forest, assessment of its status and underlying threats is important. Estimation of carbon stocks locked up in the forest is also key in designing the required climate change mitigation options. However, there is limited information on the biodiversity status and carbon storage potential of many forest reserves in Tanzania. This study assessed the tree and shrub species diversity, composition, stand structure, and carbon stock potential of the Lake Duruti Forest Reserve (LDFR). Data were collected from 40 systematically established concentric plots (0.071 ha each) covering a total forest area of 26.24 ha. A total of 48 tree and shrub species were recorded, comprising both adult individuals (DBH ? 5 cm) and regenerants (DBH < 5 cm), representing 25 plant families. Adult individuals accounted for 42 species from 23 families, while regenerants included 22 species from 15 families. The Shannon-Wiener diversity index (H?) was 3.21 for adults and 2.80 for regenerants, indicating high species diversity. The mean stem density of adult trees was 197 ± 97 stems ha?¹, with a basal area of 16.27 ± 7.30 m² ha?¹. The estimated above-ground carbon stock was 79.24 ± 35.31 Mg C ha?¹, while below-ground carbon stock was 30.86 ± 12.77 Mg C ha?¹. The absence of visible anthropogenic disturbance suggests effective conservation measures are in place. These findings highlight the ecological stability and carbon sequestration potential of LDFR and highlight the need for strategic planning to enhance biodiversity conservation and carbon stock management.